The Influence of Leadership Style on Organizational Sustainability: the Mediating Role of Knowledge - Wang, Yueying; Zhang, Ce (Journal of Global Economy, Business and Finance, 2024)
The influence of leadership style on organizational sustainability is a research area that has received much attention. A leader's style, behavior, and values can influence an organization's economic, social, and environmental performance. Studying the relationship between leadership and sustainability is important for advancing sustainability and helps guide the efforts of leaders and organizations in this area. Leadership styles and knowledge management have attracted extensive research interest as key elements of organizational success. The intersection of these two fields, especially in the literature on organizational sustainability, has attracted considerable attention from researchers. Although leadership styles and knowledge management have been extensively studied separately, their interactions and their combined impact on organizational sustainability are still relatively new areas of research. Abusive and exploitative leadership can inhibit knowledge sharing and innovation among employees, leading to knowledge hiding, which can negatively impact organizational sustainability. On the contrary, transformational and supportive leadership may promote knowledge sharing, improve the organization's ability to learn and innovate, and contribute to the realization of sustainability. This study aims to fill a research gap on the relationship between leadership styles, knowledge management, and organizational sustainability to explore in depth the role of different leadership styles on knowledge intermediation and how they collectively influence organizational sustainability. Through this research, organisational leaders, policy makers and academics will be provided with a deeper understanding, providing useful insights for practical practice and future research.